2000
DOI: 10.1073/pnas.160041997
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus inhibits amiloride-sensitive Na+channels in respiratory epithelia

Abstract: Many pathogens causing diarrhea do so by modulating ion transport in the gut. Respiratory pathogens are similarly associated with disturbances of fluid balance in the respiratory tract, although it is not known whether they too act by altering epithelial ion transport. Here we show that influenza virus A͞PR͞8͞34 inhibits the amiloride-sensitive Na ؉ current across mouse tracheal epithelium with a half-time of about 60 min. We further show that the inhibitory effect of the influenza virus is caused by the bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
124
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 43 publications
10
124
2
2
Order By: Relevance
“…Infection with H5N1, compared with seasonal H1N1, influenza virus also led to greater down-regulation of the Na,K-ATPase and CFTR transporter proteins in alveolar epithelium. Influenza virus infection was previously shown to impair alveolar fluid transport by inhibiting epithelial sodium channel activity through interaction of viral hemagglutinin (15) and matrix (16) proteins with the epithelial sodium channel. To our knowledge, ours is the first demonstration of impaired alveolar fluid clearance and protein permeability due to soluble mediators released by infected alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with H5N1, compared with seasonal H1N1, influenza virus also led to greater down-regulation of the Na,K-ATPase and CFTR transporter proteins in alveolar epithelium. Influenza virus infection was previously shown to impair alveolar fluid transport by inhibiting epithelial sodium channel activity through interaction of viral hemagglutinin (15) and matrix (16) proteins with the epithelial sodium channel. To our knowledge, ours is the first demonstration of impaired alveolar fluid clearance and protein permeability due to soluble mediators released by infected alveolar epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been recently shown that ENaC activity is down-regulated after influenza virus infection of mouse tracheal epithelia, contributing to the accumulation of edema fluid in the airway (Kunzelmann et al 2000;Matthay et al 2002). This down-regulation is dependent on viral hemagglutinin binding to a cell surface receptor, which was shown to activate phospholipase C and protein kinase C (PKC).…”
Section: Discussionmentioning
confidence: 99%
“…Apical and basolateral surfaces of the monolayer were simultaneously perfused with a solution containing (in mM) 130 NaCl, 1 CaCl 2 , 1 KCl, 1 MgCl 2 , 5 glucose, 10 HEPES, pH 7.4, maintained at 37°C. Experiments were carried out under open circuit conditions (24). Transepithelial resistance was measured by applying short (1 s) repetitive 10-A current pulses across the epithelium.…”
Section: Methodsmentioning
confidence: 99%